Diagnosis and Management of Multiple Endocrine Neoplasia Type 1 (MEN1) - Dreijerink Koen MA; Lips Cees JM (Hereditary Cancer in Clinical Practice, 2005)
Abstract Multiple endocrine neoplasia type 1 (MEN1) is an autosomal dominantly inherited disorder, characterised by the occurrence of tumours of the parathyroid glands, the pancreatic islets, the pituitary gland, the adrenal glands and neuroendocrine carcinoid tumours. Carcinoid tumours of the thymus and pancreatic-duodenal gastrinomas are the most harmful tumour types, since these tumours have malignant potential and curative treatment is difficult to achieve. MEN1 is caused by germline mutations of the MEN1 tumour suppressor gene. Mutation analysis enables mutation carriers to be identified. MEN1 patients and their family members, family members of mutation carriers and patients who are clinically suspected to be carriers of a MEN1 gene mutation are eligible for mutation analysis. MEN1-associated tumours can be detected and treated at an early stage through periodical clinical monitoring of mutation carriers.